2011
DOI: 10.1177/1741826710389405
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular disease in the very elderly: results of a cohort study in a city in southern Brazil

Abstract: Many traditional risk factors are not associated with cardiovascular mortality in the very elderly. Longer sleep duration is associated with lower cardiovascular mortality of very elderly individuals, while low blood pressure identifies very elderly individuals at higher risk of dying from cardiovascular causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…Use of medications is virtually unheard of. In Brazil, Veranópolis, in Rio Grande do Sul, is also known for exceptional longevity (59). The life habits of its inhabitants are quite similar to those of the communities cited above; one common characteristic with the Sardinians is regular wine drinking.…”
Section: Multiple Interventionsmentioning
confidence: 70%
“…The variables total cholesterol, triglycerides and having three or more of the analyzed cardiovascular risk factors (hypertension, total cholesterol, glucose and triglycerides) showed differences, with the highest prevalence in those individuals who presented both types of excess fat (total and abdominal) compared to those with only one or who did not present excess fat. Several studies have shown that the presence of certain risk factors in elderly subjects is related to a higher mortality rate 18 and higher prevalence of multimorbidity 19,20 ; however, few authors have investigated CRFs in subjects over 80 years of age. 21 Risk factors are conditions that predispose individuals to an increased risk of developing heart disease 22 , among which are included hypertension, hypertriglyceridemia, hypercholesterolemia, hyperglycemia and an excess of total and abdominal body fat.…”
Section: R R R R Results Esults Esults Esults Esultsmentioning
confidence: 99%
“…Online) 2016;49(1): [17][18][19][20][21][22][23][24][25] The quantitative variables were presented as median and interquartile values. These variables were distributed and the Mann-Whitney test used to compare according to sex, %BF and %TF (controlled for sex and age) between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation